"Missed a vaccine?" Survey on vaccine hesitancy of high-risk categories in Bologna. (20th October 2021) - Montalti, M; Rallo, F; Kregel, J; Po, G; Stillo, M; Musti, M; Pandolfi, P; Fantini, MP; Resi, D; Gori, D
Abstract: Background: Vaccine Hesitancy (VH) is considered by the WHO to be one of the ten threats of the 21st century. The Italian National Plan for Vaccine Prevention, as well as the European Action Plan, have among their objectives that of increasing the adherence to vaccinations both in general population and in categories at higher risk. It is precisely to these latter groups that the action of the Bologna Local Health Authority (LHA) has addressed targeted vaccination campaigns in recent years (e.g., DTP, HepB, PCV/PPV, RZV). Aim of our study was to investigate adherence to the proposed vaccination campaigns. Methods: An anonymous QR-code scanned survey was administered to adults during the COVID-19 vaccine campaign in February in Bologna, a city in Northern Italy. Results: A total of 2, 321 participants were enrolled, 59% of whom were female. Among healthcare workers (n = 1, 417), VH was 45.6% for Hib in 2020, 60.3% in 2019, and 68.3% in 2018; and 14.9% for HepB. Among people with chronic conditions (n = 149), 36.6% did not get the PCV/PPV vaccine. Among RZV vaccine recipients (n = 406), only 11.1% reported having been vaccinated. Women who were at least once pregnant in the last 5 years (n = 124), did not get the anti-pertussis vaccine in 41.9% of cases, and 71.8% of them refused the Hib vaccine. In general, the reasons most often given for missed vaccinations were 'I did not inform myself enough about this specific vaccine' (ranging from 16.0% for Hib for healthcare workers to 44.8% for RZV), 'I am not informed about the vaccinations I am entitled to' (27.3% for RZV, 31.8% for PCV/PPV), and 'I do not find it useful' (46.2% for Hib in healthcare workers). Conclusions: Our findings show that even in those who accept the COVID-19 vaccine, VH is high for other vaccinations campaigns run by the Bologna LHA. Targeted awareness and designed catch-up actions are needed, especially regarding this group that does not totally stand in the ranks of the so-called 'no vax'. Key messages: Vaccine Hesitancy toward other vaccines remains high among those who accept the anti-COVID-19 vaccination. A large number of hesitant respondents report either not being aware of the possibility of vaccination or not being adequately informed about the specific vaccine.